Putting housing at the heart of health reforms. Issue 1 (2014) - ,
Abstract : Purpose – The purpose of this paper is to explore the role and potential contribution of Health and Well‐being Boards from the perspective of an independent chair with senior experience in the housing sector.Design/methodology/approach – Personal reflections from chairing the Stoke Health and Well‐being Board.Findings – Only a small number of Health and Well‐being Boards are believed to have an independent chair, and it is rare to see a housing perspective represented so centrally in the composition of the Board. Against this background, this paper explores the scope for greater joint working between health, housing and social care which arises out of having senior housing representation on the Health and Well‐being Board.Originality/value – This paper offers a first‐hand account of the way in which the Stoke Health and Well‐being Board has tried to develop its thinking around joint working between health, housing and social care.